Effectiveness of PjBL Based E-module Supported by Learning Journals in improving Students' Critical and Creative Thinking Skills - Ikhtiarni, Fadhilah; Balqis, Balqis; Sari, Murni Sapta (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Effort to develop critical and creative thinking skills that 21st century students needs remain limited. Learning activities to practice these skills have not been implemented optimally and the teaching materials used also do not have indicators of these skills. Through PjBL-based electronic modules and with the help of learning journals, it is believed that students' critical thinking and creative thinking skills can be improved. This study uses two research groups, held on november till december 2022 the control class and the experimental class. The tool used includes essay questions tailored to the indicators. The ANOVA test shows that E module has a significant impact on students' critical thinking skills (α=0.00) and creative thinking (α=0.00). The e-module based on PjBL and supported by a learning journals is effective in improving both skills and is useful in teaching and learning process.